Technique and performance in classical cross-country skiing. How does different sub-techniques influence physiological responses and performance at steep uphill terrain? - Pettersen Engseth, T. (Norges Arktiske Universitet, 2018)
Background: The double poling technique has developed and further created a debate in the cross-country sport. Several athletes have seen that use of double poling without kick wax under their skis, has greater advantages than challenges in many of the trails used in competitions today. Various initiatives have therefore been put in place to ensure that diagonal stride technique retains in the classical cross country skiing. Purpose: The aim of this study was (1) to investigate the differences in physiological responses and GE at different levels of athletes (elite and non-elite skiers), while using DP and DIA technique on a treadmill, at steep (10,5 %) to very steep uphill (15%). Further, (2) investigate how the use of DP and DIA affects the performance at very steep uphill and finally (3) how the differences between two level groups (elite and non-elite) might influence the results. Method: 14 participants, 7 elite athletes (age 29 ± 4 years, body mass 77,8 ± 8 kg, height 180 ± 7 cm) and 7 non-elite athletes (age 24 ± 10 years, body mass 75,4 ± 8,4 kg, height 181 ± 7 cm) performed a submaximal test at 10.5% incline with 4 stages (DIA and DP at 8 km/h, DIA and DP at 10 km/h) while roller skiing on a treadmill. Physiological responses were examined between each stage. Further, they performed two performance tests (in DIA and DP) at 15% incline. Physiological responses and TTE were measured, both during and after each test. Results: In the submaximal test, the elite (EG) and non-elite (NEG) group performed with significantly lower physiological responses and higher GE (all p<0.05) in DIA compared to DP. Further, EG performed with significantly lower % of HRmax, Lactate and % of TSVO2peak at all sequences, lower VO2 at 8 km/h, and higher GE at DP 8 km/h compared to NEG (all p<0.05). In the performance test, both groups performed with significantly higher VO2peak and longer TTE (p<0.05) in DIA compared to DP. EG performed with significantly longer TTE (p<0.05) in both techniques compared to NEG. Conclusion: In both submaximal- and performance tests, the results indicated that both groups performed more efficient and effective in DIA compared to DP. Further, EG tended to be more efficient, and performed significant longer (TTE) in DIA and DP compare to NEG, in both the submaximal- and performance tests.